Prepregnancy Weight in Women with Type I Diabetes Mellitus: Effect on Pregnancy Outcomes - Kawakita, T.; Bowers, K.; Coviello, E.; Miodovnik, M.; Ehrlich, S.; Rosenn, B.; Khoury, J. C. (American Journal of Perinatology, 2016)
Objective This study aims to evaluate the association between prepregnancy body mass index (BMI) and adverse pregnancy outcomes in women with type 1 diabetes mellitus (DM).Methods This is a secondary analysis of a cohort of 426 pregnancies in women with type 1 DM recruited before 20 weeks gestation. Women were categorized according to prepregnancy BMI: low BMI (< 20 kg/m2), normal BMI (20 to < 25 kg/m2), and high BMI (≥ 25 kg/m2). The outcomes of interest were: spontaneous abortion (delivery < 20 weeks gestation); preeclampsia; emergent delivery for maternal indications (hypertension or placental abruption); and preterm delivery (< 37 weeks gestation). Analyses included proportional hazards and multiple logistic regression models with covariates: age, age at diagnosis of type 1 DM, previous spontaneous abortion, microvascular disease (nephropathy or retinopathy), and glycohemoglobin A1 concentrations.Results Low BMI was associated with preterm delivery. High BMI was associated with emergent delivery for maternal indications. Glycemic control as measured by glycohemoglobin A1 was associated with increased risk of spontaneous abortion, attenuating the association with low prepregnancy weight.Conclusion Prepregnancy BMI is a risk factor to be considered when caring for women with type 1 DM, in particular for preterm delivery (low BMI) and emergent delivery for maternal indications (high BMI).
Keywords: prepregnancy weight; preterm delivery; spontaneous abortion; type 1 diabetes; low BMI; high BMI